Nesting Traps to Collect Solitary Cavity-Nesting Hymenoptera - Mirwan, Hamida B. (Al-Mukhtar Journal of Sciences, 2023)
The aim of this study to survey the bees species using nesting traps, determine the diameter and material of which the nests were made. This study was conducted at the Researches and experiments Station of the Faculty of Agriculture, University of Tripoli, using nesting traps. Traps were designed with diameters of 5,8,10 mm paper and 5 mm plastic drinking straws(tubes) with 20 cm long), the traps were mounted on trees that surrounding alfalfa field. The results showed that the percentage of occupied nests, were as follows: The paper nests strews 60% of 5 mm, 5% of 8 mm, (zero) of 10 mm, and only 5% of 5 mm plastic strews. Bees identification reveled one species as alfalfa leaf-cutter bee (Megachile rotundata, F: Megachilidae - Hymenoptera).The diameter of the straw was crucial in determining the sexual ratio, straws with 5 mm of diameter as the ratio of males to females was 1♀:1♂, whether paper or plastic strews, while 8 mm was 2♀:1♂.The research recommend reusing the nests made of paper tubes with 5 mm of diameter to collect the largest number of alfalfa leaf-cutter bees to get their benefits in pollinating the alfalfa crop.